Smart Microgrid : Power Monitoring And Management System With Self-Healing Ability - Dintika, Arief Fajariandi; Penangsang, Ontoseno; Aryani, Ni Ketut (Department of Electrical Engineering ITS and FORTEI, 2025)
This research presents a smart microgrid power monitoring and management system with self-healing ability. Solar power plants have been integrated into the microgrid, which previously relied on DG and PLN power supply. However, the system’s monitoring and control are limited. This study develops an effective, efficient and reliable smart microgrid using integration of online monitoring and control system, power management system and self-healing ability. Online monitoring and control system is effectively to monitor and control the microgrid, can detect and analyze potential fault on grid at ease. Power management system is necessary to enhance efficiency and reliability to optimize power distribution. Then, with self-healing ability, enable to detect, to prevent, to isolate and to recover fault on grid automatically, make the smart microgrids more efficient and reliable. Through the Siemens TIA Portal, the study compared the simulation results of a conventional microgrid system with a smart microgrid system incorporate with online monitoring and control system, power management system, self-healing ability. Using some fault scenarios, MTTD value, MTTR value and Availability Rate value are obtained. As result, the applied smart microgrid system decrease the duration to detect and to recover fault on microgrid efficiently, thus the reliability also increased significantly.